O-009 ASPECTS Scores and DWI Volume: How well do they correlate?. (29th July 2016) - Hui, F; Bullen, J; John, S; Toth, G; Hussain, S
Abstract : Recent trials for the management of large vessel occlusion for acute ischemic stroke have demonstrated better outcomes for intervention over IV tPA alone. Ideal imaging triage remains uncertain, however CT only paradigms, volumetric paradigms, penumbral paradigms and collateral paradigms have been proposed and used. The volumetric exclusion criteria employed in EXTEND-IA and SWIFT-PRIME may have contributed to mRS 0–2 rates of 71% and 60% respectively. One of the appeals of MR estimation of irreversible "core" infarct is that it is the most accurate readily available modality. CT ASPECTS is more widely available, but may underestimate the volume of core. Statistical methods: The Pearson correlation coefficient was used to assess the amount of linear correlation between ASPECTS and DWI volume. The DWI volume values observed within each ASPECT score were then summarized. An empirical receiver operating characteristic (ROC) curve was used to summarize the accuracy of using ASPECTS to predict DWI volume less than 70 cc. The operating point furthest from the chance diagonal was selected as the optimal ASPECTS threshold and 95% Agresti-Coull confidence intervals were calculated for the sensitivity and specificity at this cut point. Results: DWI ASPECTS and DWI volume had a strong negative correlation (r = –0.76; 95% CI: –0.67, – 0.82), though there was a fair amount of variability in DWI volume within a given DWI ASPECT score. CT ASPECTS and DWI volume had a moderate negative correlation (r = –0.50; 95% CI: – 0.36, –0.62), though there was considerable variability in DWI volume for a given CT ASPECT score. In this sample, there were 105 patients with DWI volume < 70 cc and 27 with volume ≥ 70 cc. The area under the ROC curve for predicting DWI volume < 70 cc was 0.93 for DWI ASPECTS and 0.81 for CT ASPECTS. The ASPECTS thresholds which maximized the overall rate of correct classification were 5 and 8 for DWI and CT, respectively. When DWI ASPECTS > 5 was considered positive for DWI volume < 70, the estimated sensitivity and specificity were 0.88 (92/105; 95% CI: 0.80, 0.93) and 0.85 (23/27; 95% CI: 0.67, 0.95), respectively. When CT ASPECTS > 8 was considered positive for DWI volume < 70, the estimated sensitivity and specificity were 0.64 (67/105; 95% CI: 0.54, 0.72) and 0.85 (23/27; 95% CI: 0.67, 0.95), respectively. Disclosures: F. Hui: None. J. Bullen: None. S. John: None. G. Toth: None. S. Hussain: None.